Antitrichomonad Action, Mutagenicity, and Reduction of Metronidazole and Other Nitroimidazoles - Lindmark, Donald G. (1976)
Twelve 4- and 5-nitroimidazole derivatives, including metronidazole and two of its metabolites, tinidazole, dimetridazole, and nimorazole, were tested for antitrichomonad action on Tritrichomonas foetus (KV(1)) and Trichomonas vaginalis (ATCC 30001) for mutagenicity on a nitroreductase-positive (TA 100) and a nitroreductase-deficient (TA 100-FR(1)) strain of Salmonella typhimurium, as well as for the reducibility of the nitro group by T. foetus homogenates. Compounds with activity <1% of that of metronidazole are regarded as inactive. All antitrichomonad compounds induce mutations and can be reduced. S. typhimurium TA 100 gave mutations under both aerobiosis and anaerobiosis; TA 100-FR(1), however, gave mutations only under anaerobiosis. Certain compounds that are reducible, and the nonreducible derivatives, were inactive. Metronidazole and its inactive 4-nitro analogue were reduced in a four-electron process in ferredoxin- or methyl viologen-mediated reactions with the same velocity. The results underscore the role of the reduction of the nitro group in the antitrichomonad and in the mutagenic activity of nitroimidazoles.